The Influence of Brand Image, Brand Love, And Brand Trust On Brand Loyalty In Local Coffee Shop Brand Names - Widhy Tri Astuti (Publikasi Indonesia, 2023)
Brand loyalty or customer loyalty is an important concept for many companies that can bring many benefits to the company, such as repeated purchases and recommendations of that brand to others, which can then reduce marketing costs. This paper aims to test and analyze the influence of brand image, brand love, and brand trust on brand loyalty. The sample technique used in this study is a nonprobability sampling technique that is purposive sampling technique. A total of 257 pieces of data were analyzed through the Structural Equation Model (SEM) based on Partial Least Square (PLS) and using SmartPLS 3.0 Software. The data analysis technique in this study using. The results of this study show that there is a positive and significant influence of brand image, brand love, and brand trust on brand loyalty. From the data analyzed, this research supports previous research that brand image, brand love, and brand trust have a positive impact to brand loyalty.